KUALITAS PELANGGAN SEBAGAI DAMPAK DARI PENINGKATAN KUALITAS PELAYANAN DAN NILAI PELANGGAN (Studi Pada Sekolah Sepak Bola Cendrawasih Purwakarta) - Amna Mawardi (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study is given to know the impact the quality of the service has on a customer statisfaction, to know how the customer value affects the customer statisfaction, and the quality of the service and customer value of the customer statisfaction on SSB Cendrawasih Purwakarta. The study used a quantitative research model with associative descriptive methods and the sample studied was 100 respondents from the total parents of students at SSB Cendrawasih. The test method uses IBM SPSS 22. This study shows that service quality has a significant effect on the customer satisfaction, then customer value has a significant effect on customer satisfaction, and for both service quality and customer value variables have a significant effect on customer satisfaction.